Implementasi Lingkungan Bahasa A Implementasi Lingkungan Bahasa Arab Dengan Model Kurikulum Terpadu Antara Pusat Pengembangan Bahasa dan Ma'had Al-Jamiah Iain ‎Padangsidimpuan ‎ - Irsal Amin Siregar (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
The transformation of institutions from STAIN to IAIN and UIN gave birth to new problems in the scientific aspects of graduates who are sometimes ready for religious studies but weak in general science or vice versa. Arabic in the Ma'had Al-jamiah environment is a necessity because it is a tool to be used as a communication tool, so it is necessary to form biah lughoh arabiah. The purpose of this study is to determine the application of biah lughoh rabiah at Ma'had Al-jamiah IAIN Padangsidimpuan. This is a qualitative descriptive study which is carried out to produce qualitative data related to the implementation of biah lughoh Arabic.at Ma'had Al-jamiah IAIN Padangsidimpuan. The research data collection method is carried out through observation, interviews and documentation. The data analysis technique in this research is by using data triangulation. The results of this study indicate that the implementation of biah lughoh arabiah at IAIN Padangsidimpuan is carried out in an integrated manner between Ma'had Al-jamiah and the Language Development Center, where formal learning is carried out by the Language Development Center which includes all aspects of language both elements and maharoh and Ma' had Al-jamiah focused on mufrodat and kalam as daily communication needs (mumarotsah), then from the five types of Arabic environment, environment of vision (Al-Biah al-marwiyah), Auditory and visual environment (Al-biah As-syam iyyah and Al-marwiyah), social environment or teaching and learning interactions using Arabic, academic environment, psychological environment. There are two types of environment that are not maximized, namely the vision environment and audio because they still have limitations on facilities. This study concludes that the implementation of biah lughoh at IAIN Padangsidimpuan is dominant in the social, academic and psychological environment and adheres to an integrative system.